2005
DOI: 10.1016/j.jfoodeng.2004.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated life testing of frozen green beans (Phaseolus vulgaris, L.) quality loss kinetics: colour and starch

Abstract: This study uses the information derived from a computational research for the design of accelerated life testing (ALT) to implement experimentally the step stress methodology for the quantification of frozen green beans (Phaseolus vulgaris, L.) colour and starch degradation kinetics. Colour loss and starch degradation were successfully modelled, respectively, by a first-order reversible and apparent first-order kinetics, under dynamic temperature fluctuations.Results show that the step stress produces models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 10 publications
0
16
2
1
Order By: Relevance
“…Sometimes oxidation process also decreases the carbohydrate, protein and fat quality parameters. Subsequently, hydrolyzation increases the moisture content in the chutney and oxidation process fade affects colour of the chutney and Prabhakara Rao et al, 22 have reported the similar kind of changes in his studies and Martins et al, 23 found that the starch content was decreased during storage of frozen green beans. Change in fat content affects the texture of the product.…”
Section: Quality Parametersmentioning
confidence: 74%
See 1 more Smart Citation
“…Sometimes oxidation process also decreases the carbohydrate, protein and fat quality parameters. Subsequently, hydrolyzation increases the moisture content in the chutney and oxidation process fade affects colour of the chutney and Prabhakara Rao et al, 22 have reported the similar kind of changes in his studies and Martins et al, 23 found that the starch content was decreased during storage of frozen green beans. Change in fat content affects the texture of the product.…”
Section: Quality Parametersmentioning
confidence: 74%
“…The lower the reaction rate constant, lesser the degradation rate and vice versa. Martins et al, 23 and Tosun 15 has reported the rate constants for quality parameters. Graph was plotted between plotted between ln (k) vs 1/T and illustrated in the Figures 10-13.…”
Section: Quality Parametersmentioning
confidence: 99%
“…2 and 3, are obtained in our laboratories. During the accelerated shelf life tests aflatoxin was extracted from10 g of ground red pepper samples as described by O'Riordan and Wilkinson (2009) and measured with HPLC as described by Martins et al (2005). Data, which are presented in Figs.…”
Section: Methodsmentioning
confidence: 99%
“…In most cases, these experiments may take unrealistically long periods. Accelerated shelf life studies are performed under such experimental conditions where the chemical, biological, or physical phenomena, which cause the expiration of the shelf life, are accelerated with acceptable accuracy (Lee and Krocta 2002;Achour et al 2001;Hough et al 2006;Martins et al 2005;Jha et al 2010;Agrahar-Murugkar and Jha 2011). The most common methods of the spoilage acceleration use either elevated temperatures or elevated water activity or both during storage experiments (Gqaleni et al 1996;Bommakanti and Waliyar 2000;Samapundo et al 2006;Saad 2009).…”
mentioning
confidence: 99%
“…The decline of chlorophyll may be due to decreasing magnesium content during storage (Martins et al, 2005).…”
Section: Changes In Levels Of Functional Components Of Chinese Cabbagementioning
confidence: 99%